2009
DOI: 10.4031/mtsj.43.5.18
|View full text |Cite
|
Sign up to set email alerts
|

Pressure Testing: Best Practices

Abstract: Success below the seas comes from careful preparation topside. Pressure testing remains one of the most useful tools designers have available to assure their systems function as intended, whether a company chooses to have in-house pressure test capability or to work with a commercial test facility.Capt. Don Walsh, pilot of the bathyscaph Trieste on its historic two-man dive to the floor of the Challenger Deep in the Mariana Trench, said with a grin, “Successful operations depend upon a Skill-to-Luck ratio. Wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 0 publications
0
6
0
Order By: Relevance
“…Both are industrial standard test methods and are generally considered to be the most efficient methods for validating the design of prototypes. Although some other non-destructive proof tests are used in industry for qualifying buoyancy modules at a given pressure rating [ 12 ], we mainly used the ceramic sphere CS T10 samples for the pressure proof test. As previously mentioned, the applied isostatic pressure (83 MPa) corresponds to a depth rating of 3660 m below sea level with a safety factor of 3.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Both are industrial standard test methods and are generally considered to be the most efficient methods for validating the design of prototypes. Although some other non-destructive proof tests are used in industry for qualifying buoyancy modules at a given pressure rating [ 12 ], we mainly used the ceramic sphere CS T10 samples for the pressure proof test. As previously mentioned, the applied isostatic pressure (83 MPa) corresponds to a depth rating of 3660 m below sea level with a safety factor of 3.…”
Section: Discussionmentioning
confidence: 99%
“…Various characterizations were carried out to investigate such ceramic spheres in terms of structure, sphericity, buoyancy and mechanical properties. The isostatic compressive strength of the ceramic hollow spheres has been considered the most critical product criterion, as they could burst due to over pressure and result in implosions during service [ 6 , 12 ]. Hence, a proof pressure test has been deployed in this study and has demonstrated that the ceramic spheres successfully withstand a short-term pressurization without any failure or implosion.…”
Section: Introductionmentioning
confidence: 99%
“…Pressure testing remains one of the most useful tools designers have available to assure their systems function as intended (Hardy and James, 2009). In the development of the JIAOLONG deep manned submersible, the safety of the manned cabin was tested at 1.1 times of the maximum operating pressure, that is, at 78 MPa in the pressure chamber.…”
Section: Preliminary Design Of the Hybrid Unmanned Submersiblementioning
confidence: 99%
“…Pressure testing with a deep-ocean pressure chamber (DOPC) is a fast and effective method to validate the safety of deep-ocean engineering equipment [ 1 ]. To develop full-ocean-depth (FOD) submersibles, large biomimetic robotic fish, new buoyancy materials, and so forth require a DOPC with a large inner diameter and ultra-high-pressure (UHP) [ 2 ].…”
Section: Introductionmentioning
confidence: 99%